Forensic autopsy in a pathology training program - Djabourian, R; Sathyavagiswaran, L; Fishbein, M C (Archives of pathology & laboratory medicine (1976), 1998)
To review a satellite facility's autopsy experience with coroner's cases, to determine the volume and type of cases performed; and to evaluate the teaching value of forensic autopsies in a pathology residency training program. A retrospective review of 65 Los Angeles County Coroner cases performed at Cedars-Sinai Medical Center, Los Angeles, Calif, from 1992 to 1996 was undertaken. Data were retrieved from cause of death statements, medical report forms, and autopsy reports. In the 65 coroner's cases performed from 1992 to 1996, ages ranged from 6 months to 97 years. During this time period, the cases comprised 6.1% (65/1059) of all autopsies at Cedars-Sinai Medical Center and 11.3% (65/575) of autopsies excluding fetal and neonatal examinations. Manners of death in the cases were accidental (53.8%), natural (40.0%), suicide (4.6%), and undetermined (1.5%). The most common cause of death in natural deaths was related to heart disease (12/26 [46.2%]). Motor vehicle collisions were the most common cause of death (15/35 [42.9%]) in the accidental group. The remainder of the causes of death in both the natural and accidental groups encompassed a wide variety of pathologic processes and injuries. Forensic autopsies in a pathology residency training program have the potential to supplement a diminishing number of hospital autopsies. A wide variety of diseases are encountered through coroner's cases. Forensic autopsies contribute to residency training by providing experience in trauma cases and a variety of medical disorders.